General Evaluation and Energy Analysis on the Effects of Installation Faults in Air Conditioning Systems - Ergen, Ruveyda; Gürtürk, Mert (My University, 2025)
In this study, the installation faults in the condenser section of household air conditioning (AC) systems were investigated. The electricity consumption of AC systems in residential buildings has been steadily increasing, raising significant concerns. Numerous studies have been conducted to reduce the electricity consumption and emission values of these systems. However, it remains questionable whether these systems are being used and installed correctly. This study experimentally investigated the effects of installation faults in the condenser section. An energy analysis was carried out to evaluate the impact of these faults on system performance. The findings revealed that installation faults caused an increase in electricity consumption ranging from 40% to 60% compared to the baseline values. Additionally, the coefficient of performance (COP) of the AC system decreased by 48.75% due to these faults. A general evaluation was also performed to calculate the unnecessary energy consumption caused by installation faults in the condenser, considering the use of AC systems in Japan, the USA, and China. The results indicated that the annual unnecessary energy consumption due to installation faults ranged from 0.05 TWh to 1.26 TWh for each country.
Keywords: Energy; Air conditioning; AC; Installation Fault